Health maintenance and low socio-economic status: A family perspective - Claudette D. Ncho; Susan C.D. Wright (AOSIS, 2013)
The socio-economic status of people has a profound influence on health, as higher rates of morbidity and mortality are reported for individuals with lower socio-economic status. Due to the increased burden of disease, research exploring how families maintain their health in a low socio-economic situation is an urgent priority. The objective of the study was to gain an understanding of the reality families are confronted with in terms of their health due to their socio-economic status. The study was contextual, qualitative and exploratory using purposive sampling methods. The sample size was governed by data saturation and realised as 17 families (n = 17). The participants for the study were families residing in Soshanguve Extension 12 and 13, South Africa. The data collection method was self-report using a semi-structured interview. Content analysis was done according to Tesch's approach using open coding. Five themes based on the theoretical basis of the study, including age, sex and genetic constitution, individual lifestyle factors, social and community networks, living and working conditions and general socio-economic status were used. Maintaining the health of people living in a physically and psychosocially disadvantaged position requires a different approach from registered professional nurses. No community-specific intervention can be planned and implemented to reduce the burden of communicable and non-communicable disease in the community without evidence based on a family perspective.